Sedekah Kultural Dan Nilai-Nilai Islam Dalam Sedekah Serabi Di Desa Suka Dana Kecamatan Muara Pinang Kabupaten Empat Lawang - Msy Messy Puspita Sari; Mohd. Aji Isnaini; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study examines the tradition of sedekah serabi as a form of cultural charity that embodies and instills Islamic values in the lives of the people of Suka Dana Village, Empat Lawang Regency. The background of this research is based on the shifting meaning of local traditions from practices influenced by animism toward those more aligned with Islamic values, as well as the limited studies linking this tradition to cultural da’wah and the internalization of Islamic values. This study aims to analyze the implementation of sedekah serabi, identify the Islamic values contained within it, and understand the symbolic meaning of serabi in the socio-religious context of the community. This research employs a qualitative approach with a descriptive method, using data collection techniques such as observation, interviews, and documentation. Data analysis is conducted interpretatively by linking field findings with theories of cultural charity, gift exchange, and symbolic anthropology. The results show that the sedekah serabi tradition functions not only as a cultural heritage but also as an effective medium of cultural da’wah in instilling Islamic values such as sincerity, gratitude, mutual cooperation, and Islamic brotherhood (ukhuwah islamiyah). Furthermore, serabi as a symbol carries both religious and social meanings, representing simplicity, blessings, and togetherness. This tradition also strengthens social solidarity and the religious identity of the community. The contribution of this study lies in the development of cultural charity studies based on local wisdom and in providing new insights into the role of tradition as a medium for the internalization of Islamic values within society.